SPEECH INTERACTION IN CROSS-CULTURAL COMMUNICATION - Derik, I. M. (Linguistic Bulletin (Movoznavchyi Visnyk), 2016)
There has been recently witnessed a great interest of native and foreign scholars to the applied research in the field of mass communication. This research is mostly focused on the speech interaction. The up-to-datedness of the given article lies in the fact that the issue under analysis deals with the mass media means and the target audience interaction optimization under the conditions of the politically and socially active civil community formation. The complexity of the communicative process under analysis is mainly preconditioned by the specifics of its organization and technical provision. The important prerequisite of the successful mass communication is the account of such relevant factors as the target audience heterogeneous nature predetermined by its mass character, information recipients’ preferences independence from the communicators’ likings and expectations. In the situation of the Internet communication the communicators and mediators are guided not only by their own intuition and professional experience – the possibility of the feedback (Scype, e-mail, ICQ technologies) allows not only to save time for broadcasting, and also to aptly react to the recipient’s changes in the mood and use the appropriate communicative strategy. In the course of the research it has been concluded and experimentally and statistically proved that there exists a general tendency of the mass media language colloquialization. It has also been postulated that the expressive potential of the linguistic means on different levels is being widely used for the communicative strategies realization.